Novel Behaviors to the Nonlinear Evolution Equation Describing the Dynamics of Ionic Currents along Microtubules - Baskonus, Haci Mehmet; Erdogan, Fevzi; Ozkul, Arif; Asmouh, Itham (E D P Sciences, 2017)
In this work, we consider the Bernoulli sub-equation function method for obtaining novel behaviors to the nonlinear evolution equation describing the dynamics of ionic currents along Microtubules. We obtain new results by using this technique. We plot two-and three-dimensional surfaces of the results by using Wolfram Mathematica 9. At the end of this manuscript, we submit a conclusion in the comprehensive manner.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY
Keywords: Tanh-Method